2020
DOI: 10.1088/1361-6528/aba4cc
|View full text |Cite|
|
Sign up to set email alerts
|

Ultra-low permittivity porous silica-cellulose nanocomposite substrates for 6G telecommunication

Abstract: The continuously increasing demand for faster data traffic of our telecommunication devices requires new and better materials and devices that operate at higher frequencies than today. In this work, a porous composite of silica nanoshells and cellulose nanofibers is demonstrated as a suitable candidate of dielectric substrates to be used in future 6G frequency bands. The hollow nanospheres of amorphous SiO2 with outstanding electromagnetic properties were obtained by a template-assisted Stöber process, in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Melamine foam (BASF Basotect® W), ethanol (EtOH, 99.5 wt.%, Altia), ammonium hydroxide solution (NH4OH, 25 wt.%, Sigma-Aldrich) and tetraethyl orthosilicate (TEOS, ≥ 99%, Sigma-Aldrich) were used as received. Cellulose nanofibers were synthesized as described earlier [37].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Melamine foam (BASF Basotect® W), ethanol (EtOH, 99.5 wt.%, Altia), ammonium hydroxide solution (NH4OH, 25 wt.%, Sigma-Aldrich) and tetraethyl orthosilicate (TEOS, ≥ 99%, Sigma-Aldrich) were used as received. Cellulose nanofibers were synthesized as described earlier [37].…”
Section: Methodsmentioning
confidence: 99%
“…As demonstrated in earlier studies, porous structures of silica can be obtained by a large variety of sol-gel methods based on alkyl silane precursor chemistries using supercritical [32] and freeze drying [33] as well as by template-assisted synthesis on colloidal polystyrene polymers [34,35] and surfactants [36]. Furthermore, very lately, we have shown that sol-gel silica nanoshells synthesized on polystyrene nanobead sacrificial templates may be assembled into highly porous 3D networks with the help of cellulose nanofibers resulting in composites with very low dielectric permittivity and loss (εr = 1.19 ± 0.01 and tan δ = 0.011 ± 0.001 at 300 GHz) [37].…”
Section: Introductionmentioning
confidence: 99%
“…Polymer matrix composites have attracted wide attention from researchers because of their relatively simple production process and low cost [ 25 , 26 , 27 , 28 , 29 , 30 ]. PDMS is a kind of flexible organic nonmetallic polymer which is insoluble in water, easily soluble in organic solvents, has high transparency, good chemical inertia, good thermal stability, is homogeneous and is easy to operate.…”
Section: Antenna Designmentioning
confidence: 99%
“…Silica intrinsically exhibits a relatively low ε r of 3.8 and tan δ of 0.005 at 0.3 THz 18 . It can offer a much lower sintering temperature by adding calcium and sodium oxides to silica to form silicate glass.…”
Section: Introductionmentioning
confidence: 99%
“…Silica intrinsically exhibits a relatively low 𝜀 r of 3.8 and tanδ of 0.005 at 0.3 THz. 18 It can offer a much lower sintering temperature by adding calcium and sodium oxides to silica to form silicate glass. In this study, we fabricated lightweight ceramic foams by directly sintering glass hollow spheres (GHSs) at 700-900 • C. The effects of sintering temperatures on their mechanical performance, and optical and dielectric properties in terahertz frequency region were systematically investigated.…”
Section: Introductionmentioning
confidence: 99%